Fixed Point Theorem for Uncommuting Mappings - Abd, Salwa S.; Abd-ullah, Alaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we prove a theorem about the existence and uniqueness common fixed point for two uncommenting self-mappings which defined on orbitally complete G-metric space. Where we use a general contraction condition.